An Autonomous Mobile Robot Using Genetic Algorithm for Finding the Shortest Track - Thiang, Thiang; Ferdinando, Hany; Kurniawan, Ronald (Institute of Research and Community Outreach, 2001)
The paper describes an intelligent autonomous mobile robot that can find a shortest track by using a genetic algorithm %28GA%29. An 89C51 microcontroller system has been implemented to perform overall robot control including shortest track searching by using GA. An assembly code has been written for GA processes such as initial population generation%2C evaluation%2C selection and mutation. The GA chromosome is represented by a bit string. Combination between roulette wheel selection and top selection scheme are used in the system. The Mobile robot is assigned as a line tracker robot. An auxiliary PC software has been developed for process visualization and parameter transmission to the microcontroller. The experiment of the shortest track searching has been done and showed a reasonable good result. The GA process was well implemented on the microcontroller and the robot could find the shortest track from the given origin location to the target. Abstract in Bahasa Indonesia : Makalah ini menjelaskan robot mobil cerdas yang mampu mencari jalur terpendek dengan menggunakan algoritma genetika %28GA%29. Mikrokontroler 89C51 digunakan untuk mengontrol robot secara keseluruhan termasuk mencari jalur terpendek menggunakan GA. Beberapa prosedur untuk proses GA dalam bahasa assembly telah dikembangkan seperti membangkitkan populasi awal%2C evaluasi%2C seleksi dan mutasi. Kromosom GA direpresentasikan dalam bentuk bit string. Sistem ini menggunakan kombinasi dari seleksi roulette wheel dan seleksi top. Robot mobil didisain sebagai line tracking robot. Sebuah program PC bantuan dikembangkan untuk proses visualisasi dan transmisi parameter ke mikrokontroler. Percobaan untuk mencari jalur terpendek telah dilakukan dan memberikan hasil yang baik. Proses GA dapat diimlementasikan dengan baik pada mikrokontroler dan robot dapat mencari jalur terpendek dari titik asal menuju ke titik tujuan. Autonomous+mobile+robot%2C+genetic+algorithm%2C+microcontroller%2C+optimization